Obstetrics By Ten Teachers - Chamberlain, Geoffrey V P (London : Arnold ; Distributed in the Americas by Little Brown, 1995)
This edition has been extensively revised, and includes recent developments in foeto-maternal medicine, care of the newborn, haemostatic and psychiatric disorders in pregnancy and discussion of medicolegal problems in obstetrics. An ELBS/LPBB edition is available.
Includes index
Bibliography: page 361
Keywords: Obstetrics; Pregnancy